COMMERCIAL BANKING PERFORMANCE AND ECONOMIC GRPWTH: THE CASE OF TUNISIA BETWEEN 19902018 - Imet Mtir; Nizar Ben Abdallah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
In this paper, we propose to assess the efficiency scoretechniques of 10 Tunisian commercial banks for the period cover 1990 to 2018. The local banking landscape was marked, during the period studied, by significant changes following the adoption by the Tunisian government, of various financial liberalization measures as well as the period of the subprime crisis and then the revolution of 2011. Given studying the technical efficiency levels achieved by Tunisian commercial banks, we propose a non-parametric method, the approach DEA, data envelopment analysis, on the one hand, and the determination of the variables explaining the level of performance on the other. Our results allow us to conclude that the banks which obtained the best average efficiency scores are: Amen Bank (100%) and Arab Tunisian Bank (98.9%). Whereas, other banks are considered inefficient. To study the impact of banking performance indicators, a variable that measures the crisis, Equity, total assets, and total liabilities on the efficiency scores calculated by the DEA methodology, return on assets (ROA) and return on equity (ROE), we used an ECM error correction model in panel data. The results show the positive impacts of these indicators on banking performance in Tunisia.